2013
DOI: 10.1002/nau.22405
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan ameliorates urinary dysfunction in the spontaneously hypertensive rat via recovering bladder blood flow and decreasing oxidative stress

Abstract: Our data suggest that BP, BBF, and oxidative stress may be responsible for the functional changes in HT-related bladder dysfunction. Olmesartan significantly ameliorated this bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 57 publications
(129 reference statements)
1
29
1
Order By: Relevance
“…Cheng et al 16 postulated some pathomechanisms responsible for detrusor motor activity and collagen changes in urinary bladder dysfunctions. An interesting study of Shimizu et al 17 on spontaneously hypertensive rats showed that ACE inhibitors ameliorates urodynamic parameters and urinary bladder oxidative injury as compared to normal rats. Thus, telmisartan also may restore proper urinary bladder blood flow and consequently prevent from oxidative stress induction and bladder damage leading to OAB/DO.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al 16 postulated some pathomechanisms responsible for detrusor motor activity and collagen changes in urinary bladder dysfunctions. An interesting study of Shimizu et al 17 on spontaneously hypertensive rats showed that ACE inhibitors ameliorates urodynamic parameters and urinary bladder oxidative injury as compared to normal rats. Thus, telmisartan also may restore proper urinary bladder blood flow and consequently prevent from oxidative stress induction and bladder damage leading to OAB/DO.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that reactive oxygen species induce detrusor overactivity through bladder afferent pathway sensitization in rats . Our previous report also showed that bladder tissue MDA levels in SHRs were significantly higher than those in Wistar rats . Strong positive 4‐hydroxy‐2‐nonenal (a marker of oxidative stress), nuclear factor erythroid 2‐related factor 2 (transcription factor) and nerve growth factor (a biomarker of detrusor overactivity) immunoreactivities were observed in the urothelium of the SHRs .…”
Section: Discussionmentioning
confidence: 79%
“…The data from our previous studies suggested that managing BBF recovery is an important factor in the amelioration of storage symptoms and bladder dysfunction . α 1A ‐Adrenoceptor mRNA is expressed in bladder microvessels in humans and rats .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations